The Estimation of Efficacy of Nonspecific Medications Against Hemorrhagic Fevers Caused by Arenaviruses - Т. Е. Sizikova; V. N. Lebedev; S. V. Borisevich (Антибиотики и Химиотерапия, 2023)
The article presents an analysis of studies assessing the effectiveness of new nonspecific medications against hemorrhagic fevers caused by arenaviruses. The possible targets for nonspecific medications, classes of researched antiviral preparations, methods of preclinical investigation of antiviral preparations in vitro and on laboratory animals, as well as prospects for their use in healthcare at present are considered. It has been shown that the level of development of nonspecific medications against hemorrhagic fevers caused by arenaviruses is significantly inferior to those against filovirus infections. Favipiravir should currently be considered as the most effective nonspecific medication against hemorrhagic fevers caused by arenaviruses.